(untitled) (Research, Society and Development, 2020)
This study aimed to compare the type of undergraduate research published in the annals of the Brazilian Society of Dental Research (SBPqO), in the year of insertion of the National Curricular Guidelines (DCN) for Undergraduate Dental Schools, in 2002, and nine years after, in 2011. 1,720 abstracts were evaluated, from the 19th (2002) and 28th (2011) annual meetings of the SBPqO, which were categorized according to the areas of knowledge, the administrative category of the institution of higher education and the units of the Brazilian federation. It was observed that the accession of the DCN did not alter the areas of knowledge studied in the researches, and the Dental Sciences publications still the most present. There was a change in the participation of institutions in the scientific production. In 2002, most of the publications were made by state public institutions (52%). In 2011, the federal public institutions were predominant (40%). There was a better distribution in the scientific participation of the institutions from different regions, due to the reduction of dominance of Southeast region from 77.5%, in 2002, to 56.7% in 2011, and the increase of all the other regions: Midwest (6.0%), Northeast (21.1%), North (1.6%) and South (14.6%). It is concluded that the insertion of DCN might have influenced the distribution of the national scientific research, however, it did not change the technical profile of the research conducted during the undergraduate degree in Dentistry.